Belarusian – Polish Border: The Diplomacy of Cross-Border Migration - Bharti, Mukesh Shankar; Pathak, Shreesh Kumar; Mathur, Aakriti (Border Crossing, 2023)
Amidst the political conflict between the European Union (EU) and Belarus, thousands of Middle Eastern migrants have been stranded at the Belarusian-Polish border. The article analyses the border clashes and politics of various migration issues in the European Union. The circumstances have been changing tremendously since November 2021, with an influx of migrants trying to cross the Belarusian border into Poland. This article further articulates the EU’s role in solving the cross-border immigration into the Poland border. The research analyzes to understand the politically motivated humanitarian crisis that is widely understood as a response from Belarus. While classical realist theories are used to account for the mechanism of secure cross-border problems, socially-oriented theories are often invoked to characterise relaxed borders. The article aims to challenge these simplified categorisations and theories, that secure borders are a long-standing reality and that security is a more complex theoretical conceptualisation. The research describes international intervention in the immigrant crisis at the Polish border and that the European Commission and EU leaders have accused Lukashenko of deliberately aiding the smuggling of migrants from the Middle East to the Polish-Belarusian border.